A replication study confirms the association of TNFSF4 (OX40L) polymorphisms with systemic sclerosis in a large European cohort. Issue 4 (27th December 2010) - Bossini-Castillo, Lara; Broen, Jasper C A; Simeon, Carmen P; Beretta, Lorenzo; Vonk, Madelon C; Ortego-Centeno, Norberto; Espinosa, Gerard; Carreira, Patricia; Camps, María Teresa; Navarrete, Nuria; González-Escribano, María F; Vicente-Rabaneda, Esther; et al.
Abstract : Objectives: The aim of this study was to confirm the influence of TNFSF4 polymorphisms on systemic sclerosis (SSc) susceptibility and phenotypic features. Methods: A total of 8 European populations of Caucasian ancestry were included, comprising 3014 patients with SSc and 3125 healthy controls. Four genetic variants of TNFSF4 gene promoter (rs1234314, rs844644, rs844648 and rs12039904) were selected as genetic markers. Results: A pooled analysis revealed the association of rs1234314 and rs12039904 polymorphisms with SSc (OR 1.15, 95% CI 1.02 to 1.31; OR 1.18, 95% CI 1.08 to 1.29, respectively). Significant association of the four tested variants with patients with limited cutaneous SSc (lcSSc) was revealed (rs1234314 OR 1.22, 95% CI 1.07 to 1.38; rs844644 OR 0.91, 95% CI 0.83 to 0.99; rs844648 OR 1.10, 95% CI 1.01 to 1.20 and rs12039904 OR 1.20, 95% CI 1.09 to 1.33). Association of rs1234314, rs844648 and rs12039904 minor alleles with patients positive for anti-centromere antibodies (ACA) remained significant (OR 1.23, 95% CI 1.10 to 1.37; OR 1.12, 95% CI 1.01 to 1.25; OR 1.22, 95% CI 1.07 to 1.38, respectively). Haplotype analysis confirmed a protective haplotype associated with SSc, lcSSc and ACA positive subgroups (OR 0.88, 95% CI 0.82 to 0.96; OR 0.88, 95% CI 0.80 to 0.96; OR 0.86, 95% CI 0.77 to 0.97, respectively) and revealed a new risk haplotype associated with the same groups of patients (OR 1.14, 95% CI 1.03 to 1.26; OR 1.20, 95% CI 1.08 to 1.35; OR 1.23, 95% CI 1.07 to 1.42, respectively). Conclusions: The data confirm the influence of TNFSF4 polymorphisms in SSc genetic susceptibility, especially in subsets of patients positive for lcSSc and ACA.